GAMBARAN PENYIMPANAN SEDIAAN OBAT DI APOTEK X KUTA UTARA KABUPATEN BADUNG - Oviani, Gusti Ayu Oviani (Journal Pharmactive, 2023)
A Pharmacy is a pharmaceutical service facility where practice pharmacy was done by a pharmacist. The drug storage system must comply with pharmaceutical service standards because inappropriate drug storage can affect the quality of the drug. The purpose of this study was to determine the description of the storage of drug preparations at the Kuta Utara X pharmacy. This study uses a quantitative observation design. This study uses samples of all ethical and self service pharmaceutical drugs for indicators of the percentage of expired and damaged drugs, percentage of dead stock drugs, and drug void time. Drug suitability with stock cards using 100 drug samples. The data taken is then analyzed using indicators. The results showed that the suitability of drugs with card stock, namely 86% did not meet the standards (100%); Expired drug that is 0.04% already meets the standard (?0.2%), and the Percentage of dead stock of 1.22% has not met the standard (0%), and the average drug vacancy time is 2 days, it does not meet the standard (0 days).